2020
DOI: 10.1007/s11199-020-01187-1
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Adolescents’ Self-Objectification from Sexualized Video Game and Instagram Use: A Longitudinal Study

Abstract: A growing body of research has demonstrated negative effects of sexualization in the media on adolescents’ body image, but longitudinal studies and research including interactive and social media are scarce. The current study explored the longitudinal associations of adolescents’ use of sexualized video games (SVG) and sexualized Instagram images (SII) with body image concerns. Specifically, our study examined relations between adolescents’ SVG and SII use and appearance comparisons, thin- and muscular-ideal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 71 publications
0
15
0
Order By: Relevance
“…This focus on receiving feedback from peers likely increases the risk for self-objectification by encouraging adolescents to anticipate and imagine their profiles' reception. Although numerous studies have linked adolescents' and young adults' SM use to self-objectification (e.g., Manago et al, 2015;Salomon & Brown, 2020;Skowronski et al, 2020;Vandenbosch & Eggermont, 2016), adolescents experience SM-specific appearance cognitions that may have unique effects on body image and mental health beyond those detailed in objectification theory.…”
Section: Bi Appearance-related Social Media Consciousnessmentioning
confidence: 99%
See 1 more Smart Citation
“…This focus on receiving feedback from peers likely increases the risk for self-objectification by encouraging adolescents to anticipate and imagine their profiles' reception. Although numerous studies have linked adolescents' and young adults' SM use to self-objectification (e.g., Manago et al, 2015;Salomon & Brown, 2020;Skowronski et al, 2020;Vandenbosch & Eggermont, 2016), adolescents experience SM-specific appearance cognitions that may have unique effects on body image and mental health beyond those detailed in objectification theory.…”
Section: Bi Appearance-related Social Media Consciousnessmentioning
confidence: 99%
“…Longitudinal evidence suggests that adolescents' exposure to sexualized Instagram images precedes valuing of their appearance over competence, which in turn is associated with heightened selfobjectification (Skowronski et al, 2020). Beginning in childhood, girls engage in self-sexualization, or attempts to appear more sexually appealing, which is associated with greater self-objectification (Starr & Zurbriggen, 2019).…”
Section: Biii Over-valuing One's Own Appearance and Sexual Appealmentioning
confidence: 99%
“…In line with this experimental research, cross-sectional research showed that following or browsing through celebrity, fashion, beauty and health/fitness accounts (so all appearancefocused) related to body dissatisfaction and other body image issues among young women (Cohen et al, 2017;Seekis et al, 2020). In addition, one of the rare longitudinal survey studies in the social media/body image field showed that frequent exposure to sexualized Instagram images (i.e., body-emphasizing posts of scantily dressed young adults in different contexts) indirectly predicted body surveillance six months later in a two-wave design (Skowronski et al, 2021).…”
Section: Exposurementioning
confidence: 98%
“…Research is needed to clarify whether the relations between sexualized media and self-objectification are similar among boys and girls (Moradi, 2010). So far, studies have found that female and male adolescents’ use of sexualized traditional media (Vandenbosch & Eggermont, 2012, 2015), and SII use (Skowronski et al, 2020) predict self-objectification via appearance-ideal internalization, with no evidence of a moderating effect of gender. However, these studies did not take the gender of the sexualized media subjects into account, which may also be relevant for the relation between media use and self-objectification.…”
Section: Sexualized Media Use and Self-objectificationmentioning
confidence: 99%